Antonio Candido’s Argentine Scheme” - Amante, Adriana (Literatura e Sociedade, 2009)
The essay explores some ideas proposed by Antonio Candido in Literatura e sociedade in connection to his own work and to some other fundamental texts of Argentine literary criticism. The goal of the essay is to think again – from the point of departure of the decisive contribution of the Brazilian critic – some problems also developed in literary texts of that other country.